2019
DOI: 10.1108/jpif-04-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the DCF and German income approach

Abstract: Purpose The majority of institutional investors in Germany use the German income approach (GIA) while investors abroad prefer the discounted cash flow (DCF). The debate around the two methods has been largely theoretical, lacking large-scale empirical evidence. The paper aims to discuss this issue. Design/methodology/approach The analysis consisted of a performance comparison and hedonic regressions based on ordinary least squares. Fitted GIA and DCF values were obtained for all observations in the data set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The study revealed that Swedish valuers utilized discounted cash flow method as their main method of commercial property valuation, but their usage of direct market comparison method has increased. Reinert (2019) analyzed the debate over the German income approach (GIA) and DCF models. The research included a performance comparison as well as hedonic regression using ordinary least squares.…”
Section: Rental Income Cash Flow In Enugumentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed that Swedish valuers utilized discounted cash flow method as their main method of commercial property valuation, but their usage of direct market comparison method has increased. Reinert (2019) analyzed the debate over the German income approach (GIA) and DCF models. The research included a performance comparison as well as hedonic regression using ordinary least squares.…”
Section: Rental Income Cash Flow In Enugumentioning
confidence: 99%
“…Reinert (2019) analyzed the debate over the German income approach (GIA) and DCF models. The research included a performance comparison as well as hedonic regression using ordinary least squares.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The simplified methods although being better, are prone to more valuer bias as the valuer must decide what information to exclude if the simplified version of the valuation is chosen. Valuation methods can also vary slightly from country to country and thus need to be followed when a valuation is taking place in another county (Reinert, 2019). The norms of a country can have further effects on the way in which the valuer makes decisions and the rules of thumb they use (Bellman & Öhman, 2016).…”
Section: Literature Review Traditional Valuation Modelsmentioning
confidence: 99%
“…This method is a cash-based financial model where the various prospective assumptions and specific timing of contractual events are explicit inputs. The method sums up all the future net cash flows associated with the subject property (Reinert, 2019). Those future cash flows are discounted into present value using the appropriate discount rate.…”
Section: Literature Review Traditional Valuation Modelsmentioning
confidence: 99%
See 1 more Smart Citation